Iot-Based Soil Moisture Monitoring And Automatic Watering System - Thomas Mahendra; Muhammad Ihsan (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
This research aims to design and implement an Internet of Things (IoT)-based soil moisture monitoring and automatic watering system using an ESP32 microcontroller. This system was developed to improve the efficiency of plant watering by reducing water usage, time, and human effort. A soil moisture sensor is used as the main input to detect soil moisture levels, while the ESP32 serves as a control center and data processor. Soil moisture data is sent in real-time to the IoT platform and can be monitored and controlled remotely through the Blynk application. A relay module is used as a connection between the ESP32 and the water pump to regulate the automatic watering process. All hardware components are housed in an acrylic casing and the system is powered by a 9V battery to operate the water pump. Test results show that the soil moisture sensor has a good level of accuracy in detecting soil conditions. The automatic watering system is able to respond quickly to changes in humidity, where the water pump is active when the humidity is below the threshold and stops when the soil conditions are optimal. Based on these results, the developed system is declared to work well and is suitable for use as an IoT-based smart irrigation solution.